Co-Integration dan Contagion Effect antara Pasar Saham Syariah di Indonesia, Malaysia, Eropa, dan Amerika Saat Terjadinya Krisis Yunani - Ikrima, Tara Ninta; Muharam, Harjum (JDM (Jurnal Dinamika Manajemen), 2014)
The objective of the study was to analyze the Greeces crisis impacts toward the movement of Islamic stock prices in Indonesia, Malaysia, USA, and Europe. Moreover, this study also analyzed co-integration and contagion effect which occurred during the period. VAR (Vector Auto Regressive) and VECM (Vector Error Correction Model) with eviews 6 were used to test the hypothesis as the statistical analysis tools. The data of this study were the weekly closing stock price indices taken from the representatives of Islamic stock markets of each country; JII in Indonesia, DJIMY in Malaysia, DJIM in USA, and MSCI in Europe. The result showed that the Greeces crisis did not give any influence toward the movement of Islamic stock prices in USA, Malaysia, Indonesia, and Europe. However; there were co-integration and contagion effect which influenced on Islamic stock prices in those four regions at Greeces crisis time.